Relationship Between Clinical Manifestations and Antibody Serum in Outbreaks Anthrax - Redhono, Dhani (Institute of Topical Disease, 2015)
Introduction: Anthrax is a zoonotic disease that often affects the grass-eating animals, which occurs due to the entry of spores into the bodies of animals and can be transmitted to humans. This disease often appear in certain seasons and occurs in endemic areas, including Indonesia. Cutaneous anthrax is the clinical manifestations that often arise on outstanding events in the area. This study aims to determine how the relationship between the clinical manifestations of the serum antibodies in people who are exposed to anthrax. Material and methods: This study is an observational cross sectional analytic approach, in people exposed to anthrax to assess the clinical manifestations and antibody serum Anthrax. Results: Obtained in this study respondents were 101 people with a history of contact with animals suffering from anthrax. The number of respondents with the highest age distribution was 31 to 40 years by 42%, and most were female gender, which is 57.7%, the highest level of education is 74% finished elementary school. Forty-four percent of working as a housewife. Risk factors are the most direct contact with and consume the flesh of animals as much as 34.6%. Results of Ig G antibody serum showed 50% negative, 15.4 borderline and 34.6% positive. Clinical manifestations that occur in the skin as much as 13.5%, that is the eschar on all respondents and 92.8% showed positive Ig G. While 86.5% did not show any clinical signs of anthrax, of that number 25.5% with Ig G positive, 16.6% and 57.7% showed borderline negative with p 0.02. Conclusion: There was a significant association between the clinical manifestation with antibody serum anthrax. But also found apositive Ig G without the appearance of clinical signs in the skin.